2020
DOI: 10.1016/j.ejps.2019.105099
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsions and thermosensitive nanoemulgels of phenytoin and fosphenytoin for intranasal administration: Formulation development and in vitro characterization

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Afterward, “intranasal drug delivery for neurodegenerative, neuropsychiatric, and other neurological disorders (cluster 1 and cluster 3)” have progressively gained importance around 2015, and some areas remain the hotpots until today, for example, “neuroinflammation (AAY = 2017.90) ( Rhea et al, 2020 ),” “mesenchymal stem cell (AAY = 2017.62)” ( Aguilera et al, 2021 ; Vaes et al, 2021 ), and “mild cognitive impairment (AAY = 2016.85) ( Craft et al, 2012 ).” Also, it needs to be noted that keywords in “cluster 2: the study of nasal drug delivery systems” had the largest AAY compared with other clusters, and the keywords of “nanocarriers (AAY = 2018.22) ( Rehman et al, 2019 ),” “nanostructured lipid carriers (AAY = 2018.11) ( Agbo et al, 2021 ),” “loaded chitosan nanoparticles (AAY = 2017.52) ( Zhao et al, 2017 ),” and “PLGA nanoparticles (2017.41) ( Nanaki et al, 2020 )” were mainly found in the early years. These results indicate that the research focus of this field has shifted from “cluster 4: pathways and mechanisms of intranasal delivery” to “cluster 2: the study of nasal drug delivery systems, especially the nanostructured and nano-sized carrier systems” ( Ali et al, 2010 ; Battaglia et al, 2018 ; Pires et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterward, “intranasal drug delivery for neurodegenerative, neuropsychiatric, and other neurological disorders (cluster 1 and cluster 3)” have progressively gained importance around 2015, and some areas remain the hotpots until today, for example, “neuroinflammation (AAY = 2017.90) ( Rhea et al, 2020 ),” “mesenchymal stem cell (AAY = 2017.62)” ( Aguilera et al, 2021 ; Vaes et al, 2021 ), and “mild cognitive impairment (AAY = 2016.85) ( Craft et al, 2012 ).” Also, it needs to be noted that keywords in “cluster 2: the study of nasal drug delivery systems” had the largest AAY compared with other clusters, and the keywords of “nanocarriers (AAY = 2018.22) ( Rehman et al, 2019 ),” “nanostructured lipid carriers (AAY = 2018.11) ( Agbo et al, 2021 ),” “loaded chitosan nanoparticles (AAY = 2017.52) ( Zhao et al, 2017 ),” and “PLGA nanoparticles (2017.41) ( Nanaki et al, 2020 )” were mainly found in the early years. These results indicate that the research focus of this field has shifted from “cluster 4: pathways and mechanisms of intranasal delivery” to “cluster 2: the study of nasal drug delivery systems, especially the nanostructured and nano-sized carrier systems” ( Ali et al, 2010 ; Battaglia et al, 2018 ; Pires et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, it needs to be noted that keywords in "cluster 2: the study of nasal drug delivery systems" had the largest AAY compared with other clusters, and the keywords of "nanocarriers (AAY 2018.22) (Rehman et al, 2019)," "nanostructured lipid carriers (AAY 2018.11) (Agbo et al, 2021)," "loaded chitosan nanoparticles (AAY 2017.52) (Zhao et al, 2017)," and "PLGA nanoparticles (2017.41) (Nanaki et al, 2020)" were mainly found in the early years. These results indicate that the research focus of this field has shifted from "cluster 4: pathways and mechanisms of intranasal delivery" to "cluster 2: the study of nasal drug delivery systems, especially the nanostructured and nano-sized carrier systems" (Ali et al, 2010;Battaglia et al, 2018;Pires et al, 2020).…”
Section: Analysis Of Changes In Research Hotspotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been reported in other studies. For example, Fatouh et al [14] observed a slight increase in the particle size of agomelatine-loaded SLN (167.7 ± 0.42 nm) after incorporation in an in situ gel (175.75 ± 1.10 nm), and Pires et al [16] verified an increase in the droplet size of a fosphenytoin-loaded nanoemulsion (216.4 ± 10.5 nm) after incorporation in a thermosensitive gel (219.7 ± 26.8 nm).…”
Section: Particle Size Pdi and Zpmentioning
confidence: 99%
“…A fast drug release was achieved from nanoemulsion with 60% of fosphenytoin, which has the potential to treat acute pain episodes, while nanoemulsion with 90% fosphenytoin and in situ fosphenytoin-loaded nanoemulsion hydrogel exhibited a prolonged drug release, showing potential for the management of nasal wound healing, inflammatory reactions, and tissue remodelling. 112 Ahmad et al developed a naringenin-loaded nanoemulsion and an in situ-based nanoemulsion hydrogel for nose-to-brain delivery to improve drug bioavailability. Naringenin is a flavonoid compound with potential for the management of AD due to its anti-inflammatory and antioxidative effects.…”
Section: Current Strategies To Improve the Treatment Of Alzheimer’s Diseasementioning
confidence: 99%